Crystal Quality and Light Output Power of GaN-Based LEDs Grown on Concave Patterned Sapphire Substrate - Wu, YewChung Sermon; Isabel, A. Panimaya Selvi; Zheng, Jian-Hsuan; Lin, Bo-Wen; Li, Jhen-Hong; Lin, Chia-Chen (My University, 2015)
The crystal quality and light output power of GaN-based light-emitting diodes (LEDs) grown on concave patterned sapphire substrate (CPSS) were investigated. It was found that the crystal quality of GaN-based LEDs grown on CPSS improved with the decrease of the pattern space (percentage of c-plane). However, when the pattern space decreased to 0.41 mu m (S0.41-GaN), the GaN crystallinity dropped. On the other hand, the light output power of GaN-based LEDs was increased with the decrease of the pattern space due to the change of the light extraction efficiency.